2011
DOI: 10.2169/internalmedicine.50.5147
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pyogenic Liver Abscess Infected with Fusobacterium necrophorum Depicted by Microscopy and Confirmed by Tissue Culture

Abstract: A 40-year-old man was admitted with a continuous high grade fever accompanying a relatively large solitary liver abscess with septations. A puncture of the abscess revealed gram-negative rods that could be identified histologically as Fusobacterium necrophorum, which was later confirmed by tissue culture. The patient was switched to meropenem and penicillin, and cured of the infection. Fusobacterium necrophorum is a rare bacterium causing potentially fatal liver abscesses in humans. Clinicians should bear Fuso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…A total of 11 cases of PLA derived from dental disease reported between 1987 and 2013, based on our search of PubMed (Table) (3)(4)(5)(6)(7)(8)(9). Fusobacterium and Streptococcus are reported to be major species of causative bacteria of PLA arising from dental infection and were also detected on abscess fluid cultures in our cases; these bacteria are also known to be normal oral flora.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 11 cases of PLA derived from dental disease reported between 1987 and 2013, based on our search of PubMed (Table) (3)(4)(5)(6)(7)(8)(9). Fusobacterium and Streptococcus are reported to be major species of causative bacteria of PLA arising from dental infection and were also detected on abscess fluid cultures in our cases; these bacteria are also known to be normal oral flora.…”
Section: Discussionmentioning
confidence: 92%
“…For a single abscess over 5 cm in diameter, catheter drainage is preferred over needle aspiration, and some even prefer surgical intervention over percutaneous drainage 6. Surgical drainage is also appropriate for multiple abscesses, loculated abscesses, abscesses with viscous content that can block the drain tube and underlying diseases that require surgical management 6…”
Section: Discussionmentioning
confidence: 99%
“…A colonoscopy, performed as part of the work up for a liver abscess (as there might have been a relation with colonic neoplasm6), was normal.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few cases of necrobacillosis with no clear sources (3,26). Nozawa et al reported a case of liver abscess infected with Fusobacterium necrophorum without pharyngeal infections or IJV thrombosis (27). Furthermore, according to Nohrstrom et al, necro-bacillosis may be accompanied by abscesses without any apparent venous thrombosis (28).…”
Section: Discussionmentioning
confidence: 99%